1995
DOI: 10.1159/000188672
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Course and Outcome of Late Acute Rejection Episodes in Living-Related-Donor Renal Allograft Recipients

Abstract: We prospectively monitored clinical data and renal function at monthly intervals in 165 patients who had received living-related-donor renal allografts in our institution between January 1981 and December 1991 and had a functioning allograft for 1 year or longer. During a mean follow-up period of 47.2 (range 13-155) months, 32 patients (17.2%) developed late acute rejections, of which 14 (43.7%) were asymptomatic. Amongst the symptomatic late acute rejections, worsening of hypertension was the commonest findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…It has been reported that the relative risk for graft loss with one AR episode versus no AR episode was 2.7, and multiple AR episodes increased the relative risk to 7.8 [4, 5]. With an increase in the number of AR episodes, the response to antirejection therapy became worse and the rate of complete response decreased [6].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the relative risk for graft loss with one AR episode versus no AR episode was 2.7, and multiple AR episodes increased the relative risk to 7.8 [4, 5]. With an increase in the number of AR episodes, the response to antirejection therapy became worse and the rate of complete response decreased [6].…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of LAR has varied between studies from 2.5 to 38% [17–22]. Wrenshall et al [20] report an incidence of 2.5 to 6.5% of AR episodes after 1 yr. Rao and Rose [17] observed that 15% of patients developed AR between 1 and 2 yr post‐transplant; the rate falling to 2% between 5 and 6 yr. Also, a very high incidence (38%) has been quoted where protocol biopsies have been employed [22].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, no studies supporting corticosteroid regimens in TCMR have including histological confirmation of resolution. [22][23][24][26][27][28] In our study, although patients with borderline TCMR were more likely to demonstrate complete resolution of rejection on FUB compared to grade ≥1A TCMR, 32% had no improvement and a further 15% had worse rejection despite treatment. A similar proportion with grade ≥1A TCMR (46%) had no treatment response to the initial standard treatment whatsoever.…”
Section: Discussionmentioning
confidence: 46%
“…There are also reports exploring longer duration of IV corticosteroid treatment for 5 or 6 days, 25 but these have not been subjected to comparative trials to evaluate their efficacy relatively to 3‐day regimens. Importantly, no studies supporting corticosteroid regimens in TCMR have including histological confirmation of resolution 22–24,26–28 . In our study, although patients with borderline TCMR were more likely to demonstrate complete resolution of rejection on FUB compared to grade ≥1A TCMR, 32% had no improvement and a further 15% had worse rejection despite treatment.…”
Section: Discussionmentioning
confidence: 52%